A stakeholder-based risk assessment and intervention framework for international construction projects: A meta-network perspective. Issue 2 (4th September 2019) - Wang, Tao; Gao, Shangde; Liao, Pinchao; Ganbat, Tsenguun; Chen, Junhua
Abstract : Purpose: The purpose of this paper is to construct a two-stage risk management framework for international construction projects based on the meta-network analysis (MNA) approach. A plethora of international construction studies seems to assume risks as independent and therefore, risk intervention strategies are usually critiqued as ineffective. Design/methodology/approach: In the risk assessment stage, a multi-tiered risk network structure was developed with the project objectives, risk events, risk factors and stakeholders, and critical risk factors were selected based on a series of calculations. In the risk intervention stage, targeted risk intervention strategies were proposed for stakeholders based on the results of the first stage. A highway construction project in Eastern Europe was selected as a case study. Findings: The results showed that 17 risk factors in three categories – external, stakeholder-related and internal – are critical, and the project manager, construction management department, supplier and contract department are the most critical stakeholders that affect the entire project performance. Based on the critical risk factors and project stakeholders, targeted risk intervention strategies were proposed. The risk assessment results of MNA were found to be more reliable and consistent with the project conditions than the risk matrix method; the risk intervention strategies of MNA can effectively address project objectives. Originality/value: This study modeled risk priorities based on risk associations and put forward a new method for risk management, supplementing the body of knowledge of international construction. The results of this study are of critical importance in management practices.